Proactive and Collaborative Strategies to Boost Customer-Brand Engagement and Experience: A Complexity Theory Approach - Bağcı, Rıfgı Buğra; Taşçıoğlu, Mertcan; Bağcı, Rıfgı Buğra (Routledge Journals, Taylor & Francis Ltd., 2024)
The online grocery industry’s swift expansion and intensecompetition underscore the urgency to tackle sustainablebusiness and cost issues while adapting to consumer trendsrequires higher prices for continued profit. Utilizing complexitytheory, the present study aims to explore the impact of pro-active and collaborative strategies on customer-brand engage-ment and experience, ultimately fostering an increasedwillingness to pay a premium. Accordingly, the results(n ¼ 406) show that proactive customer orientation and valueco-creation significantly increase the customer experience andfoster higher levels of customer-brand engagement, ultimatelyincreasing willingness to pay more. Notably, the mediationanalysis reveals that customer-brand engagement serves as amediating factor in the relationship between customer experi-ence and the willingness to pay more. This study contributesto the online grocery shopping literature by integrating pro-active and collaborative strategies and investigates customerexperience and engagement through the lens of complexitytheory.
Keywords: Collaborative strategies; Complexity theory; Online grocery shopping; Onlineshopping; Proactivestrategies